The Nimbus 6 Electrically Scanning Microwave Radiometer: data rescue - Emil Haaber Tellefsen; Rasmus Tage Tonboe; Wiebke Margitta Kolbe; Julienne Stroeve (2024)
The Nimbus 6 Electronic Microwave Radiometer (N6ESMR) was a Single frequency, 37 GHz, dual polarisation radiometer aboard the Nimbus 6 meteorological satellite and was active between June 22, 1975 and August 11, 1977. Its data is one of the few available sources for satellite sea ice monitoring, and might thus be used to expand the record of sea ice behavior if processed. However, the original level 1 radiance data were never archived, meaning that the only available data source is printed grayscale data images intended for manual analysis, which was stored on 70 mm film strips as both positives and negative. Scanned TIF images of these were made available in 2022 at the Goddard Earth Science Data Information and Services Center (GES DISC). For this project, a framework has been developed for recovering parts of the data from the TIFs using various image analysis and machine learning techniques all described in the corresponding paper. The utilized code is available at https://github.com/EHTellefsen/N6ESMR_rescue, while the resulting dataset is available here as NetCDF4-files for both positive an negative images from between 12 June 1975 and 31 March 1976. Full description of the contents of the files is available within the files.